2016
DOI: 10.1016/j.actamat.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization and nanocrystallization of silicon under shock compression

Abstract: High-power, short-duration, laser-driven, shock compression and recovery experiments on [001] silicon unveiled remarkable structural changes above a pressure threshold. Two distinct amorphous regions were identified: (a) a bulk amorphous layer close to the surface and (b) amorphous bands initially aligned with {111} slip planes. Further increase of the laser energy leads to the re-crystallization of amorphous silicon into nanocrystals with high concentration of nano-twins. This amorphization is produced by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 72 publications
4
70
1
Order By: Relevance
“…This is partially confirmed in a very recent paper by Zhao et al, 21 in which defect accumulation induced amorphization was observed locally in bulk c-Si under dynamic shock compression, resulting in a complex distribution of a-Si.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is partially confirmed in a very recent paper by Zhao et al, 21 in which defect accumulation induced amorphization was observed locally in bulk c-Si under dynamic shock compression, resulting in a complex distribution of a-Si.…”
Section: Discussionsupporting
confidence: 72%
“…10 As such, in the absence of direct evidence, the necessity of the Si-II phase during the CAT process is uncertain, and has in fact been challenged by several research groups. 13,14,21 In an effort to directly observe the response of c-Si to indentation, Minor et al 22 carried out indentation tests inside TEM. They found no phase transformation and only dislocationmediated metal-like plastic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Applying classical nucleation theory we can obtain the pressure and shear-stress dependence of the nucleation barrier, as explained previously by Zhao et al (31),…”
Section: Discussionmentioning
confidence: 99%
“…Despite the simplicity and effective 1D treatment, this model explained many experimental results on PTs in DAC and RDAC and developed our intuition on the interaction between PTs and plasticity at the nanoscale. Due to the generic character of the model, qualitative conclusions from its application have been used by other groups to interpret their experimental findings in high pressure torsion [99,103], mechanochemistry and ball milling [108,109,110] and shock-induced amorphization in Si [111].…”
Section: Pts Under High Pressure and Compression And Shearmentioning
confidence: 99%
“…Alternative boundary conditions-free lateral surfaces-, have been applied for an exploratory study of the shearinduced PT at zero pressure in [8]. Still, results obtained in [64], again due to their generic character, were applied in [103] for the interpretation of experiments on high pressure torsion, in [112] on PTs in nanomaterials under mechanical loading, and in [111] on shock-induced amorphization in Si.…”
Section: Pts Under High Pressure and Compression And Shearmentioning
confidence: 99%